THE IMPORTANCE OF PLAYFULNESS IN VOLLEYBALL LESSONS - de Oliveira, Lorisval; Antônio de Araújo Leite Filho, Marcos (RENEF, 2022)
The objective of this article was to analyze the importance of a ludic approach in volleyball classes. This work was a field study of qualitative approach, the target audience consisted of four teachers of the state education system of the Florêncio Ferreira Lima State School and Rodrigues Alves State School, both in Monte Azul/MG. They answered a questionnaire; the sampling was not probabilistic. As an instrument of data collection a short questionnaire was addressed to the teachers. The data were analyzed and the results were analyzed through descriptive statistics through percentage values. It was found that ninety percent always try to approach their classes in a playful way. In view of the research carried out, the importance of a playful class that aims at the participation of all can be noticed, one that approaches a methodology different from the traditional ones, where volleyball classes in which the fundamentals and the perfection of movements are not the most important.